Intensify or Alleviate? Measurement of the Impact of China’s Facility Agriculture on Greenhouse Gas Emissions: Comparative Analysis Based on Cucumber Industry - Xialing Chu; Linxiu Zheng; Jie Li; Pengfei Cheng (Agronomy)
Facility agriculture can increase production efficiency and alleviate resource constraints. Its developmental level has become one of the most important indicators of the level of agricultural modernization worldwide. The Chinese government has attached great importance to the development of facility agriculture in recent years. Since 2020, the “No. 1 Document” has continuously emphasized and deployed the development of facility agriculture. Global climate change has greatly impacted the traditional agricultural production that is vulnerable to weather changes, while the development of facility agriculture can to some extent alleviate the limitations of climate conditions on agricultural production. However, it is unclear whether facility agriculture can help alleviate the adverse effects of global climate change, i.e., reducing greenhouse gas emissions. In view of this, in this research, based on the data from the latest National Compilation of Cost and Benefit Data on Agricultural Products in 2022, the greenhouse gas emissions and carbon emission indicators of open-field and greenhouse cucumber productions in China were measured using the life cycle assessment method (the full cycle of agricultural ecosystems). The results show that the average total greenhouse gas emissions (4572.67 kgCE·hm−2) from China’s facility cucumber production system are significantly higher than those from traditional open-field production methods (8712.86 kgCE·hm−2), with net greenhouse gas emissions from facility cucumber cultivation being on average 98.78% higher than those from open fields. Combining indicators such as land carbon intensity, carbon productivity, and carbon economic efficiency, it can be concluded that the sustainability of facility cucumber cultivation is lower than that of open-field cucumber cultivation. Additionally, considering the comprehensive differences in economic development, resource endowments, planting methods, and technological inputs across different regions, there are significant inter-provincial variations in the greenhouse gas composition, carbon sequestration, carbon ecological efficiency, carbon productivity, and carbon economic efficiency of both open-field and facility cucumbers. However, overall, carbon productivity shows a certain geographical proximity effect, with an increasing trend from south to north for open-field cucumbers. The above research findings provide direct evidence for the development of facility agriculture in China. Based on these measurement results and analytical conclusions, this paper further explores how to reduce carbon emissions and promote emission reduction in facility agriculture, providing reliable empirical support for policy implementation by relevant authorities and academic research.